THE USE OF 'PROPS' IN TEACHING ACCOUNTING. - Van Voorhis, Robert H. (The Accounting Review, 1953)
Abstract Accounting lectures can be made more understandable and more interesting to the students by the use of suitable "props" illustrating practical accounting situations. Students often have difficulty understanding the operation of a petty cash fund and visualizing the petty cash count. After the subject has been studied in the text and discussed in class, it creates immediate interest among the students for the instructor to produce a petty cash box and ask one of them to audit the fund in the presence of its custodian. The student should be instructed to behave exactly as if he were in a client's office. The audience should be cautioned not to offer suggestions during the course of the count. All should be given a chance to view and examine the contents of the box so that they may comment on the auditor's findings after he has finished. This experience will impress the petty cash count on the minds of the students as no amount of talking about it can do. Other "props" can frequently be obtained to enliven the presentation of ace counting procedures. Worthless securities may be used by students in making a securities count. The handling of actual stocks and bonds gives the student a sense of seriousness and will command his attention much more fully than a textbook problem can do.